Towards a New European Bauhaus—Challenges in Design Education - Barros, P C; Duarte, A.P.; Perestrelo, Margarida (Towards a New European Bauhaus—Challenges in Design Education, 2024)
This chapter discusses how mutualist associations (MAs) in Portugal can contribute to communities and regions’ sustainability in terms of health, well-being, welfare, and resilience, as stipulated in the United Nations’ Sustainable Development Goals 3, 11, and 17. The research was based on a conceptual model of human beings’ role on this planet and its consequences for diverse territories. This study integrated multi-and transdisciplinary perspectives and concentrated on MAs’ contributions in Portugal to determine whether and how these associa-tions can provide solutions that can be used to update the New European Bauhaus. The findings are based on a literature review, national secondary data, and case study of two MAs. The results reveal that these organizations are key players in efforts to promote territories’ sustainability and communities’ health, well-being, and welfare, acting in partnership with other regional stakeholders. Acknowl-edging these associations’ significant contribution to communities and regions’ well-being and development could encourage other groups to create other sim-ilar organizations. Their activities would contribute to varied communities and territories’ sustainable development, thereby generating multiple gain spirals.